Trends of traditional postpartum practices utilizing local medicinal plants from Kota Belud, Sabah - Fadzilah Awang-Kanak (Penerbit UMS, 2024)
Ethnogynaecology is a field of study that focuses on managing gynaecological-related issues including postpartum care, through the utilization of traditional healers, tribal communities, and local practitioners. Traditional knowledge of Sabah medicinal plants is insufficiently documented, despite Sabah is home to more than 42 different ethnics and rich in flora diversity. This study aims to record medicinal plants from Kota Belud, that have been used as traditional remedies during postpartum care for mothers. This work also provides brief details of plant parts used as traditional remedies and the administrating methods. A total of nine plant species, namely Aloe vera, Bambusa sp., Benincasa hispida, Cosmos caudatus, Curcuma longa, Curcuma xanthorrhiza, Ficus septica, Momordica charantia, Zingiber zerumbet, were traditionally employed for postpartum care, a period spanning 40 to 90 days post-partum. The ethnopharmacological data gathered directly from these communities has the potential to serve as a substantial foundation for future research in natural product development and drug discovery.